CULTURAL TOURISM AS A WAY FORWARD – A CRITICAL EVALUATION OF TOP-DOWN TOURISM MANAGEMENT IN MALAYSIA - Lim, Dr. Benny (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2019)
Malaysia is one of the fastest-growing developing nations in Southeast Asia. Over the years, the management of tourism at the federal government level underwent several major revamps. The current Ministry of Tourism and Culture has been in force since May 2013, with different departments and agencies managing museums, tourism, cultural heritage, and the arts. Despite the seemingly good economic contribution of tourism to Malaysia’s economy, its performance is actually pale in comparison to its two closest neighbors – Singapore and Thailand. This paper seeks to critically evaluate the current top-down tourism management in Malaysia, specifically in terms of its organizational structure and management processes. The extended marketing mix by Booms and Bitner is adopted as the framework for discussions. Three key findings were identified from the twofold qualitative research. First, MOTAC needs to enhance visitors’ experience of its Malaysia Tourism Centre through improving the center’s facilities, as well as incorporating digital technologies. Next, there is a lack of cultural diversity and motivations within MOTAC. Finally, cultural tourism could be a way forward to elevate Malaysia’s tourism to the next level.